2017
DOI: 10.1007/s00421-017-3582-4
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal fatty acid-binding protein and gut permeability responses to exercise

Abstract: PurposeIntestinal cell damage due to physiological stressors (e.g. heat, oxidative, hypoperfusion/ischaemic) may contribute to increased intestinal permeability. The aim of this study was to assess changes in plasma intestinal fatty acid-binding protein (I-FABP) in response to exercise (with bovine colostrum supplementation, Col, positive control) and compare this to intestinal barrier integrity/permeability (5 h urinary lactulose/rhamnose ratio, L/R).MethodsIn a double-blind, placebo-controlled, crossover des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
95
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(110 citation statements)
references
References 38 publications
10
95
3
2
Order By: Relevance
“…Following both EHSTs, I‐FABP increased by approximately 50% or 0.800 ng ml −1 . This response is comparable to numerous similar duration/intensity exercise protocols, such as: 45‐to‐60 min of ~70% watt max normothermic cycling (van Wijck et al, , [61%, Δ 0.306 ng ml −1 ] 2012, [61%; Δ 0.179 ng ml −1 ] and 20–30 min of ~80% VO 2max running (Barberio et al, [46%, Δ 0.297 ng ml −1 ]; March et al, [72%; Δ 0.350 ng ml −1 ]). In comparison, far greater elevations in I‐FABP have been shown following 90–120 min of moderate‐intensity running performed in the heat (30°C; Morrison, Cheung, & Cotter, [663%; Δ 0.203–0.806 ng ml −1 ]; Snipe et al, [288%, Δ 0.897 ng ml −1 ]; 2018 [432%, Δ 1.230 ng ml −1 ].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Following both EHSTs, I‐FABP increased by approximately 50% or 0.800 ng ml −1 . This response is comparable to numerous similar duration/intensity exercise protocols, such as: 45‐to‐60 min of ~70% watt max normothermic cycling (van Wijck et al, , [61%, Δ 0.306 ng ml −1 ] 2012, [61%; Δ 0.179 ng ml −1 ] and 20–30 min of ~80% VO 2max running (Barberio et al, [46%, Δ 0.297 ng ml −1 ]; March et al, [72%; Δ 0.350 ng ml −1 ]). In comparison, far greater elevations in I‐FABP have been shown following 90–120 min of moderate‐intensity running performed in the heat (30°C; Morrison, Cheung, & Cotter, [663%; Δ 0.203–0.806 ng ml −1 ]; Snipe et al, [288%, Δ 0.897 ng ml −1 ]; 2018 [432%, Δ 1.230 ng ml −1 ].…”
Section: Discussionsupporting
confidence: 71%
“…Given general logistical constraints of the urine/serum DSAT, the majority of relevant evidence has attempted to validate (correlate) this method against more practical GI barrier integrity biomarkers. These studies generally report significant, though weak correlations ( r = 0.4–0.6) between basal corrected (Δ) DSAT (urine 5 hr) and I‐FABP responses directly following moderate GI barrier integrity loss (March et al, ; van Wijck et al, , ). In this study, the DSAT did not correlate with any other GI integrity biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed Morrison et al (2014) have reported an increase in I-FABP of 563% following 90 min of cycling and running in 30°C with an end core temperature of 38.75°C, while Barberio et al (2015) reported an increase of only 46% following 26 min of running in 40 degrees with an end core temperature of 39.0°C at a similar intensity. In support of the hypothesis that the magnitude of exercise induced intestinal damage is not related to environmental temperature we have combined the present group mean data with data from other studies that simultaneously report the post-exercise change in I-FABP in combination with end exercise core temperature, participants V O 2max (indicative of training status), and exercise duration and intensity (Morrison et al 2014;Barberio et al 2015;March et al 2017;McKenna et al 2017;Snipe et al 2018a). There was a significant correlation between environmental temperature (range 22°C to 40°C) and end exercise core temperature (range 38.2°C to 39.6°C) (r=0.79, p=0.011), however; there was no significant correlation between the magnitude of intestinal damage and core temperature (r=0.3, p=0.43), suggesting that other factors contribute to the extent of damage.…”
Section: Discussionsupporting
confidence: 70%
“…19 Previous studies have demonstrated that gut barrier dysfunction after gut IR is mainly caused by metabolic disorders and destruction of enterocytes, which can benefit from exercise. 30,31 However, the effects of irisin on the intestinal barrier have not been elucidated to date. In this study, F I G U R E 7 Genipin abolished the protective role of irisin in gut IR.…”
Section: Discussionmentioning
confidence: 99%